Military innovation and intrastate warfare: Portuguese artillery and sieges during the Wokou raids of the mid-sixteenth century - Noordam, Barend (The first world empire, 2021)
Portuguese weapons started reaching China in the early sixteenth century. Among them were two cannon designs, the breech-loading berço, and the muzzle-loading falcão, which were immediately and enthusiastically appropriated by the Chinese. This chapter analyses the extent to which these weapons changed Chinese siege warfare during the middle of the sixteenth century. In contrast to the earlier Chinese usage of cannons during sieges, Portuguese cannons were used against enemy equipment and fortifications, not merely against enemy combatants. They replaced earlier types of artillery, like catapults and large crossbows, in these roles. Furthermore, they might have become part of a Parkerian challenge-and-response dynamic in this way, despite the presence of impregnable walls. However, the Portuguese cannons did not initiate the Chinese desire for heavier and larger ordnance. More powerful indigenous pieces were already being manufactured before the arrival of the Portuguese, but the berço and falcão appear to have stimulated and cross-fertilized indigenous innovation. The analysis of siege warfare and cannon development, moreover, shows that both the emergence of heavier indigenous designs and the efflorescence of Portuguese-derived cannons seem to have happened in a context of intrastate warfare spanning the first half of the sixteenth century, not during conditions of sustained interstate competition. Therefore, to explain processes of military innovation in Ming China, we need to look beyond the Eurocentric assumptions of the interstate competition model. In terms of the military revolution debate, the Portuguese weapons could have led to several far-reaching changes in army size, firepower, cost, and resource extraction capabilities. This potential notwithstanding, a lack of institutional continuity characterized the government response to internal challengers, and the latter also failed to pose a perennial and consistent threat. These political and institutional factors probably mitigated Portuguese cannons’ having a revolutionary impact on Chinese (siege) warfare.